Metal halide with multiple excitation sources and preparation method thereof
By synthesizing and preparing novel manganese-based metal halides (CTP)2MnCl4 and (BTP)2MnCl4, the problem of insufficient excitation capacity of existing materials is solved, efficient photoluminescence and force electroluminescence performance is achieved, and high resolution is shown in X-ray imaging.
Patent Information
- Application Number
- CN202411948834.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Most of the existing manganese-based metal halide materials can only be excited by a single or dual excitation source, and there are problems of insufficient performance in the fields of force electroluminescence and X-ray detection.
Two new manganese-based metal halides (CTP) 2MnCl4 and (BTP) 2MnCl4 were designed and synthesized. Single crystals were prepared by solvent volatilization method, their crystal structure was analyzed, fluorescence spectroscopy, quantum yield and thermal stability were measured, and the luminescence mechanism was analyzed.
The strong green light emission under multiple excitation sources was achieved, with photoluminescence quantum yields reaching 98.5% and 88.4%. It showed strong stress luminescence phenomenon during fracture, had excellent force-stimulating luminescence performance, and achieved high resolution in X-ray imaging.
Smart Images

Figure CN119798329A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of manganese metal halides, and in particular to a metal halide with multiple excitation sources and a preparation method thereof. Background Art
[0002] In the past decade, CsPbX3 (X=Cl - ,Br - , I - ) are becoming potential star materials for light-emitting diodes, solar cells, radiation detection and other optoelectronic devices due to their low-cost wet chemical synthesis and excellent optoelectronic properties, such as high carrier mobility, suitable band gap, high photoluminescence quantum yield (PLQY) and strong X-ray absorption. However, the toxicity and poor stability of lead halide perovskites have greatly restricted their further development, so finding alternatives to lead-based halides has become a hot research topic.
[0003] In this regard, environmentally friendly and low-cost organic-inorganic hybrid zero-dimensional (0D) Mn 2+ As a new type of luminescent material, manganese-based metal halides can show excellent optical properties under the stimulation of ultraviolet light / blue light, X-rays and mechanical force, which makes them develop rapidly in the field of optoelectronic devices, especially in the fields of wide color gamut backlight display, flexible wearable optoelectronic products, X-ray detection and anti-counterfeiting encryption. However, most of the manganese-based metal halides reported so far can only be excited by a single excitation source or dual excitation sources, and there are few reports of manganese-based metal halides that can be excited by ultraviolet light / blue light, X-rays and respond to mechanical force at the same time. Therefore, it is of great scientific and practical value to explore manganese-based metal halides with multiple excitation sources at the same time and explore their applications in various scenarios.
[0004] In the field of mechanoluminescence, mechanoluminescent materials have been applied in fields such as information storage, structural damage sensors, pressure sensors and anti-counterfeiting devices. Unlike the common elastic-mechanical luminescence mechanism in doped inorganic compounds (such as ZnS:Cu, ZnS:Mn and CaZnOS:Mn), metal halides usually exhibit fracture-mechanical luminescence, and their mechanoluminescence phenomenon is usually so weak that it is difficult to detect. Although there are many reports on mechanoluminescent manganese-based metal halides, the detailed fracture luminescence process and fracture luminescence mechanism still need further study. In the field of X-ray detection, the indirect X-ray imaging method is widely used, in which the scintillator is the key component of X-ray detection. Although various types of materials have been used for X-ray scintillators, existing organic and inorganic scintillating materials still have many problems and limitations, such as the difficulty in growing inorganic crystals and their strict requirements on hygroscopicity, and the anisotropic scintillation of organic crystals. Low-dimensional metal halide scintillators represented by lead halide have become promising X-ray scintillators due to their large X-ray absorption coefficient, easy solution processing, and high scintillation yield.
[0005] However, the commercial development of lead halide scintillators has been plagued by problems such as poor lead stability and toxicity. Most of the recently reported 0D lead-free and efficient metal halide scintillators are based on copper, manganese, tin and antimony inorganic cations. Among them, Mn(II)-based metal halides have become the most promising candidate materials for X-ray imaging due to their advantages such as low toxicity, negligible self-absorption, high photoluminescence quantum yield (PLQY) and high scintillation rate. In the field of wearable optoelectronics, current wearable devices are mostly focused on the application of APbX3. The obstacles to practical application are the instability of lead halide perovskites under light, humidity and temperature, the leakage of harmful lead ions and the difficulty in fabricating uniform flexible films at large scale and high productivity. Encapsulating metal halides in polymers, porous alumina films, or fabricating metal halide-transparent glass composites have been variously developed to stabilize metal halides and impart advanced optoelectronic functions. However, these methods require some complex synthesis and processing steps (such as spin coating process, high temperature quenching process), and it is difficult to obtain large-area metal halide flexible films. In recent years, electrospinning technology has been proven to be one of the most ideal methods for preparing perovskite luminescent fiber films, and the prepared luminescent films or devices can be easily assembled into large-area, flexible and wearable optoelectronic products. Therefore, the large-scale synthesis of smart wearable optoelectronic flexible films by combining metal halides with electrospinning technology has good application prospects. Summary of the invention
[0006] In order to comprehensively solve the above problems, the present invention aims to design a metal halide with multiple excitation sources. The present invention synthesized two new manganese-based metal halides (CTP)2MnCl4 and (BTP)2MnCl4 (CTP is (2-chlorobenzyl)triphenylphosphonium ion, BTP is benzyltriphenylphosphonium chloride ion), analyzed their crystal structures, measured their fluorescence spectra, quantum yields and thermal stability, and analyzed the luminescence mechanism.
[0007] (CTP)2MnCl4 and (BTP)2MnCl4 exhibit defect-assisted tetracoordinated Mn at 513 and 516 nm, respectively. 2+ The strong green light emission produced by the dd transition has a photoluminescence quantum yield (PLQY) of up to 98.5% and 88.4%, respectively. The two scintillators show strong stress luminescence when the crystal breaks, and the flexible film prepared by them also achieves excellent force-stimulated luminescence. Based on the commercial CsI:Tl scintillator, the light yields of (CTP)2MnCl4 and (BTP)2MnCl4 scintillators are calculated to be as high as about 89,000 and 49,000 photons / MeV, and the (CTP)2MnCl4@PDMS scintillator screen also achieves X-ray imaging with a resolution of up to 9.1lp / mm. Subsequently, (CTP)2MnCl4 was combined with PMMA to prepare a large-area luminescent fiber membrane of 20cm×25cm, which can be used in wearable luminous clothing for emergency rescue at night, information recording, emergency lighting and other fields.
[0008] In order to achieve the above objectives, the first aspect of the present invention provides a metal halide with multiple excitation sources, with the structural formula A2[MnCl4], wherein A is CTP or BTP, CTP is a (2-chlorobenzyl)triphenylphosphonium cation, and BTP is a benzyltriphenylphosphonium cation.
[0009] The second aspect of the present invention provides a method for preparing a metal halide with multiple excitation sources, comprising:
[0010] Step 1: Dissolve MnCl2 and substance A in methanol at room temperature to form a clear and transparent solution;
[0011] Step 2: Slowly evaporate the solution in step 1 in an oven for 48 hours to prepare a light green block A2[MnCl4] single crystal.
[0012] Preferably, in step 1, the molar ratio of MnCl2 to substance A is 1:2.
[0013] Preferably, the temperature of the oven in step 2 is 40°C.
[0014] Preferably, the substance A in step 1 is any one of (2-chlorobenzyl)triphenylphosphonium chloride or benzyltriphenylphosphonium chloride.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The (CTP)2MnCl4 and (BTP)2MnCl4 synthesized in the present invention show defect-assisted four-coordinated Mn at 513 and 516 nm respectively. 2+ The strong green light emission produced by the dd transition has a photoluminescence quantum yield (PLQY) of up to 98.5% and 88.4%, respectively. The two scintillators show strong stress luminescence when the crystal breaks, and the flexible film prepared by them also achieves excellent force-stimulated luminescence. Based on the commercial CsI:Tl scintillator, the light yields of (CTP)2MnCl4 and (BTP)2MnCl4 scintillators are calculated to be as high as about 89,000 and 49,000 photons / MeV, and the (CTP)2MnCl4@PDMS scintillator screen also achieves high-resolution X-ray imaging of up to 9.1lp / mm. Subsequently, (CTP)2MnCl4 was combined with PMMA to prepare a large-area luminescent fiber membrane of 20cm×25cm, which can be used in wearable luminous clothing for emergency rescue at night, information recording, emergency lighting and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0018] In the attached picture:
[0019] Figure 1 In the figure, a. Photographs of (CTP)2MnCl4 under fluorescent lamp (top) and 365nm ultraviolet light excitation (bottom); b. Photographs of (BTP)2MnCl4 single crystal under fluorescent lamp (top) and 365nm ultraviolet light excitation (bottom); c. Scanning electron microscope image of (CTP)2MnCl4 single crystal, which contains the elemental distribution of Cl, P and Mn elements; d. Scanning electron microscope image of (BTP)2MnCl4 single crystal, which contains the elemental distribution of Cl, P and Mn elements; e. Ellipsoid diagram of the molecular structure of (CTP)2MnCl4 (50% probability ellipsoid); f. Ellipsoid diagram of the molecular structure of (BTP)2MnCl4 (50% probability ellipsoid); g. Crystal structure of (CTP)2MnCl4; h. Crystal structure of (BTP)2MnCl4.
[0020] Figure 2In the figure, a. excitation and emission spectra of (CTP)2MnCl4; b. excitation and emission spectra of (BTP)2MnCl4; c. relationship between excitation power and emission intensity of (CTP)2MnCl4; d. relationship between excitation power and emission intensity of (BTP)2MnCl4; e. fluorescence decay spectra of (CTP)2MnCl4 and (BTP)2MnCl4 at room temperature; f. fluorescence quantum yields of (CTP)2MnCl4 and (BTP)2MnCl4 at room temperature; g. UV-vis absorption spectra of (CTP)2MnCl4 and (BTP)2MnCl4 at room temperature; h. photoluminescence mechanism diagram of (CTP)2MnCl4 and (BTP)2MnCl4.
[0021] Figure 3 a. Temperature-dependent PL spectrum of (CTP)2MnCl4; b. Temperature-dependent PL spectrum of (BTP)2MnCl4; c. Thermogravimetric analysis and differential thermal analysis of (CTP)2MnCl4; d. Thermogravimetric analysis and differential thermal analysis of (BTP)2MnCl4; e. Photoluminescence stability of (CTP)2MnCl4 in air, 80°C, 25°C and 78% relative humidity; f. Photoluminescence stability of (BTP)2MnCl4 in air, 80°C, 25°C and 78% relative humidity.
[0022] Figure 4 In the figure, a. Mechanoluminescence and photoluminescence spectra of (CTP)2MnCl4; b. Mechanoluminescence and photoluminescence spectra of (BTP)2MnCl4; c. Force response of (CTP)2MnCl4 over time; d. Force response of (BTP)2MnCl4 over time; e. PL and PLE spectra of (CTP)2MnCl4 single crystal before and after fracture at room temperature; f. PL and PLE spectra of (BTP)2MnCl4 single crystal before and after fracture at room temperature; g. Schematic diagram of mechanoluminescence mechanism; h. Photos of (CTP)2MnCl4 and (BTP)2MnCl4 force-responsive films under different conditions.
[0023] Figure 5a. Absorption coefficient-photon energy relationship of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators; b. Radioluminescence spectra of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators under the same conditions; c. Comparison of scintillation light yield of (CTP)2MnCl4 and (BTP)2MnCl4 with common scintillation crystals; d. Absorption coefficient-photon energy relationship of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators under the same conditions; e. Absorption coefficient-photon energy relationship of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators under the same conditions; f. Absorption coefficient-photon energy relationship of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators under the same conditions; f. Absorption coefficient-photon energy relationship of (CTP)2MnCl4, (BTP)2MnCl4 and CsI:Tl scintillators under the same conditions; g ... f. The linear relationship between the luminescence spectrum and luminescence intensity and X-ray irradiation dose in the range of 14-926μGyair / s; f. The linear relationship between the luminescence intensity and X-ray irradiation dose of (CTP)2MnCl4 and (BTP)2MnCl4 at low doses; g. Photos of different objects under natural light, X-rays and (CTP)2MnCl4@PDMS scintillation screen; h. MTF curve of (CTP)2MnCl4@PDMS scintillation screen measured by the bevel edge method.
[0024] Figure 6 In the figure, a. Schematic diagram of the electrospinning process; b. Photo of (CTP)2MnCl4@PVA fiber membrane under fluorescent light; c. Photo of (CTP)2MnCl4@PVA fiber membrane under 254nm ultraviolet light; d. SEM image of (CTP)2MnCl4@PVA fiber membrane; e. Diameter distribution statistics of (CTP)2MnCl4@PVA fibers; f. SEM image and element distribution map of (CTP)2MnCl4@PVA; g. Photo of wearable luminous clothes prepared with (CTP)2MnCl4@PVA fiber membrane; h. Luminous bracelet; i. Luminous numbers; j. Emergency sign. DETAILED DESCRIPTION
[0025] The following combination Figure 1-Figure 6 The preferred embodiments of the present invention are described. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] Embodiment 1:
[0027] A metal halide with multiple excitation sources; the structural formula is A2[MnCl4]; wherein: A is a monovalent organic phosphonium ion; A is CTP or BTP; CTP is a (2-chlorobenzyl)triphenylphosphonium cation; BTP is a benzyltriphenylphosphonium cation.
[0028] Embodiment 2:
[0029] A method for preparing metal halides with multiple excitation sources; comprising
[0030] Step 1: Dissolve 1 mmol of MnCl2 and 2 mmol of substance A (substance A is (2-chlorobenzyl)triphenylphosphonium chloride or benzyltriphenylphosphonium chloride) in 10 ml of methanol at room temperature to form a clear and transparent solution;
[0031] Step 2: Slowly evaporate the solution of step 1 in a 40°C oven for 48 hours; prepare a light green block A2[MnCl4] single crystal.
[0032] Result analysis:
[0033] 1. Crystal growth and structure:
[0034] (CTP)2MnCl4 and (BTP)2MnCl4 single crystals were grown by solvent evaporation method; both showed transparent light green color under sunlight and bright green luminescence under 365nm ultraviolet light excitation ( Figure 1 A and Figure 1 b). Single crystal of (CTP)2MnCl4 (such as Figure 1 (shown in the upper right corner of a); the dimensions are 1.0cm×1.2cm×1.7cm; the shape is a regular polyhedron.
[0035] SEM and element distribution ( Figure 1 Medium c and Figure 1 d) shows that the P, Cl, and Mn elements in the synthesized (CTP)2MnCl4 and (BTP)2MnCl4 single crystals are uniformly distributed in the crystals, proving that the synthesized crystals have high phase purity. The crystal structures of (CTP)2MnCl4 and (BTP)2MnCl4 were determined by single crystal X-ray diffraction (SCXRD); their crystal structure data are shown in Table 1. Figure 1 Zhongehe Figure 1 As shown in f; each (CTP)2MnCl4 and (BTP)2MnCl4 molecular formula contains two organic cations and one [MnCl4] 2- Tetrahedral anion; in terms of spatial structure; [MnCl4] 2- The tetrahedron is surrounded by organic cations CTP + / BTP + Separate; each [MnCl4] 2- There are no common vertices between them; a zero-dimensional structure is formed at the molecular level. The closest distances between Mn and Mn in (CTP)2MnCl4 and (BTP)2MnCl4 are 10.4233 and ( Figure 1 Medium g and Figure 1 h); the larger Mn-Mn distance can effectively prevent Mn 2+ Non-radiative transitions between ions; suppressing emission quenching; improving their photoluminescence quantum yield.
[0036] Table 1. (CTP)2MnCl4 and (BTP)2MnCl4 single crystal X-ray diffraction data
[0037]
[0038] 2. Photoluminescence properties
[0039] The excitation and emission spectra of (CTP)2MnCl4 and (BTP)2MnCl4 show that ( Figure 2 Middle a, Figure 2 b); In the range of 200-500nm, there are 6 main excitation peaks that can excite (CTP)2MnCl4 and (BTP)2MnCl4 crystals; corresponding to Mn 2+ of 6 A1→ 4 T1( 4 F)(287 / 289nm), 6 A1→ 4 E( 4 D)(359nm), 6 A1→ 4 T2( 4 D)(381nm), 6 A1→ 4 A1( 4 G), 4 E( 4 G)(433nm), 6 A1→ 4 T2( 4 G)(450nm), 6 A1→ 4 T1( 4 G) (468nm) transition; the strongest excitation peak is located at 287 / 289nm; under different excitation wavelengths; a narrow-band (~46nm) green light emission of 513 / 516nm is generated.
[0040] In order to further study the luminescence dynamics of (CTP)2MnCl4 and (BTP)2MnCl4, we measured their emission spectra at different powers. The variable power spectra of (CTP)2MnCl4 and (BTP)2MnCl4 can be well fitted by a single exponential function ( Figure 2 Middle c, Figure 2 d); at high power density; their PL intensity begins to gradually weaken and tends to stabilize (because the number of electrons captured by the defect energy level is limited); which indicates that its luminescence process is likely related to the defect-related excited state; these defect energy levels can serve as long-lived energy storage reservoirs for electrons; compensating electrons to the emission center.
[0041] Their fluorescence decay lifetimes were measured by time-resolved spectroscopy; the results showed that the fluorescence lifetimes of both were in the millisecond range, 3.147 and 3.118 ms ( Figure 2 e); the longer fluorescence decay lifetime is mainly caused by the spin-forbidden characteristics of the metal center d–d transition. This lifetime is higher than that of common tetrahedral bromides; this is because the spin-orbit coupling of chlorine atoms is lower than that of bromine atoms. Both also have higher photoluminescence quantum yields; 98.5% and 88.4% respectively (Figure 2f); this is higher than most manganese-based metal halides reported in the literature.
[0042] In addition, the UV-visible absorption spectrum ( Figure 2 Mn was observed in 2+ The characteristic transition peak has an absorption tailing phenomenon, which further proves the existence of defect energy levels. For bulk ionic metal halides, halide / metal vacancies, interstitials and antisites are common structural defects when forming bulk components, while due to the high crystallinity of the material, surface defects can be ignored. Shallow defects and deep defects formed in the band gap play different decisive roles in the photophysical processes of the material. It is known that deep defects may be non-radiative recombination centers, shorten carrier lifetimes, and deteriorate optical properties, while shallow defects may be PL centers. Shallow defects are usually formed in the presence of halide vacancies, which are close to the valence band edge and may serve as defect energy levels to locate photogenerated carriers of radiative recombination.
[0043] The defects of (CTP)2MnCl4 and (BTP)2MnCl4 are reasonably attributed to the shallow defects caused by Cl vacancies. The photoluminescence mechanism of (CTP)2MnCl4 and (BTP)2MnCl4 is as follows Figure 2 As shown in h, under the excitation of ultraviolet light or blue light, the electrons are first excited to the shallow defect energy level at the edge of the valence band, and then further excited to the Mn 2+ different excited state energy levels; then return to the ground state to produce green light emission.
[0044] 3. Stability
[0045] Firstly, the thermal stability of (CTP)2MnCl4 and (BTP)2MnCl4 was tested by variable temperature spectroscopy; their variable temperature spectra showed that ( Figure 3 Middle a, Figure 3(b) In the process of temperature rising from 298K to 478K, the luminescence intensity gradually decreased to 19.1% and 18.4% of the initial value. In addition, with the increase of temperature, the emission peak position also produced a significant blue shift and was accompanied by an increase in the half-peak width. The increase in the half-peak width may be related to the reduction of electron-phonon coupling; and the blue shift of PL may be due to the filling of defect states with lower energy; this has also been reported in many other metal halides.
[0046] Subsequently, the thermal stability of (CTP)2MnCl4 and (BTP)2MnCl4 was further tested by thermogravimetric method; Figure 3 Middle c, Figure 3 As shown in (d). (CTP)2MnCl4 and (BTP)2MnCl4 have almost no weight loss at 537K and 477K respectively, and there is no endothermic or exothermic peak; the endothermic peaks around 540K and 482K in the DTA results correspond to the melting points of (CTP)2MnCl4 and (BTP)2MnCl4, showing high thermal stability. In addition, we further measured the stability of (CTP)2MnCl4 and (BTP)2MnCl4 when stored in water, heat and air. Within one month of exposure in air environment;
[0047] The spectral intensity of (CTP)2MnCl4 and (BTP)2MnCl4 still remains above 90% of the initial value; after being placed in an environment of 80℃ for 1 month, the spectral intensity of (CTP)2MnCl4 and (BTP)2MnCl4 still remains above 86% of the initial value; after being stored at 25℃ and 78% relative humidity for one month, the spectral intensity still remains above 80% of the initial intensity ( Figure 3 Zhonge, Figure 3 (f)
[0048] 4. Mechanical luminescence characteristics and applications
[0049] (CTP)2MnCl4 and (BTP)2MnCl4 single crystals can also emit very dazzling green light under the action of stress; this green light can be observed very clearly even in sunlight. When stress is slowly applied to (CTP)2MnCl4 and (BTP)2MnCl4 single crystals to break the crystal, very strong green light emission will be generated at the moment of crystal breaking; such as Figure 4 Middle a, Figure 4 As shown in the inset in b. In order to further explore the mechanoluminescence process; we further studied the mechanoluminescence spectra of (CTP)2MnCl4 and (BTP)2MnCl4 ( Figure 4 Middle a, Figure 4b); their mechanoluminescence spectra show green emission peaks at 513 and 516 nm, respectively, which are almost consistent with the photoluminescence peak positions. Similar TL and PL spectra indicate that their green emission comes from Mn 2+ The same transition. Figure 4 Middle c, Figure 4 In the middle (d), we can see that the mechanoluminescence signal has a good response over time. In order to further explore the mechanoluminescence process, we compared the spectra of the bulk crystal before fracture and the microcrystal after fracture ( Figure 4 Zhonge, Figure 4 (f)
[0050] The results show that the intensity of the excitation and emission spectra before and after the fracture has changed dramatically. 6 A1→ 4 T1( 4 F) There is no obvious change in the emission spectrum intensity produced by the transition; the emission spectrum intensity produced by the other several transitions has dropped significantly; the strongest excitation peak changes from 450nm to 284nm; this shows that the energy inside the crystal has changed significantly before and after the fracture.
[0051] Figure 4 In the figure g, it is a schematic diagram of the mechanism of mechanoluminescence. Under the stimulation of mechanical force, hydrogen bonds are broken on the fracture surface of the crystal, and opposite charges are generated on the fracture surface. Subsequently, the energy released by the recombination of electrons and holes is transferred to the same excited state as in the photoluminescence process, thereby generating the same green light emission as in photoluminescence. Since the breaking of hydrogen bonds is not always continuous on a macroscopic scale, although the breaking of hydrogen bonds can be easily achieved from bulk crystals to microcrystals, and thus strong mechanoluminescence is observed, it is not easy to break hydrogen bonds by further grinding from microcrystals, which also explains the non-repeatability of the observed mechanoluminescence.
[0052] In addition, since the excitation source of mechanoluminescence comes from the energy released by the recombination of internal electrons and holes when the crystal breaks, when the crystal breaks completely from the bulk crystal to the microcrystal, the energy released by the recombination of internal electrons and holes during a large number of fractures is used to excite mechanoluminescence, resulting in a large energy difference between the bulk crystal and the microcrystal, which further explains the huge difference in the intensity of the excitation and emission spectra between the bulk crystal and the microcrystal. Subsequently, we combined (CTP)2MnCl4 and (BTP)2MnCl4 with silica gel and successfully prepared two flexible force-responsive films (Figure 4h), both of which showed a uniform milky white color under sunlight, bright green under 254 ultraviolet light, and very obvious green light emission under the stimulation of stress, which is expected to be used for information encryption and anti-counterfeiting identification.
[0053] 5.Radioluminescence properties and applications
[0054] (CTP)2MnCl4 and (BTP)2MnCl4 also have excellent radioluminescence performance and have broad application prospects in the field of X-ray detection and imaging. We first calculated the X-ray absorption coefficients of (CTP)2MnCl4, (BTP)2MnCl4 and the typical scintillator CsI:TI in a wide photon energy range based on the photon cross section database ( Figure 5 (a) (CTP)2MnCl4 and (BTP)2MnCl4 have similar molecular formulas, which makes their absorption rates basically the same. In addition, due to their low density, their absorption rates in the medical digital radiography region (i.e., 18-30keV) are slightly lower than those of CsI:Tl. (CTP)2MnCl4 and (BTP)2MnCl4 single crystals exhibit bright green luminescence under X-ray excitation ( Figure 5 b inset); and further measured the RL spectrum; it showed narrow-band green light emission at 516 / 520nm respectively (Figure 5b); similar PL and RL spectra indicate that the same radiative recombination channels occurred under X-ray and UV light excitation. Taking the commercial CsI:Tl single crystal scintillator (light yield of about 54000photons / MeV) as a reference; we further evaluated the light yield of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals. The response of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals is about 1.64 and 0.91 times that of CsI:Tl; the calculated light yield of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals is about 89000 and 49000photons / MeV; this is better than most of the commonly used inorganic scintillators and those reported in the literature ( Figure 5 (c).
[0055] In addition, the RL spectrum intensity of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals shows good linear response in the range of X-ray dose increasing from 214μGyair / s to 926μGyair / s. Figure 5 Middle d, Figure 5 e). According to the linear response relationship of the RL spectrum at low X-ray doses, when the signal-to-noise ratio (SNR) is 3, the calculated detection limits of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals are 0.205 and 0.248 μGyair / s, respectively (Figure 5f), which are much lower than the 5.5 μGyair / s required for X-ray medical diagnosis. In view of the excellent scintillation performance of (CTP)2MnCl4 and (BTP)2MnCl4 single crystals, we took (CTP)2MnCl4 as an example to further verify its potential in actual X-ray imaging. A flexible scintillating screen prepared by mixing (CTP)2MnCl4 powder with PDMS is used for X-ray imaging. Figure 5 As shown in G1, we use a plastic capsule as the first target object. The plastic capsule contains a metal spring. Usually, the spring cannot be observed under visible light. However, due to the different absorption capabilities of the metal spring and the plastic capsule to X-rays, we observed a contrast image under X-ray irradiation, showing that there is a clear metal spring inside.
[0056] To further demonstrate the capabilities of the X-ray imaging system, we used different chips as target objects. Under X-ray irradiation, some details of the microchip's internal circuitry were revealed ( Figure 5 g234); demonstrated the potential of (CTP)2MnCl4@PDMS scintillating screen in industrial flaw detection. In order to characterize the spatial resolution of X-ray imaging; the modulation transfer function (MTF) of the image was obtained by the slant edge method. Figure 5 As shown in h, when the MTF value is 0.2, the spatial resolution of the (CTP)2MnCl4@PDMS scintillating screen is 9.1lp / mm, showing great potential in practical X-ray imaging applications such as security inspection, nondestructive testing and medical radiography.
[0057] 6. Application of multifunctional fiber membrane
[0058] Based on the huge application potential of electrospinning technology in the field of wearable optoelectronics and the outstanding optical properties and excellent stability of (CTP)2MnCl4, the application of (CTP)2MnCl4 in multifunctional wearable luminous fiber membranes was further explored. Figure 6 Figure a shows the schematic diagram of the preparation process of (CTP)2MnCl4@PMMA luminescent fiber membrane. (CTP)2MnCl4 is filtered through a 100-mesh screen and mixed evenly with a gelled polymethyl methacrylate (PMMA) aqueous solution; it is sucked up with a syringe and passed through a single-nozzle electrospinning device to make (CTP)2MnCl4@PMMA fibers evenly spun on a rotating drum covered with oil paper; after spinning for a period of time; a large-area fiber membrane of 20cm×25cm can be obtained ( Figure 6 b); the fiber membrane can be prepared repeatedly; under 254nm ultraviolet light ( Figure 6 c); it shows uniform green light emission. The microscopic morphology of (CTP)2MnCl4@PMMA fiber membrane was further analyzed by SEM; the fiber membrane is composed of a spatial network structure spun from countless tiny fibers ( Figure 6 d); The diameter distribution diagram shows that the average size of the fibers in the (CTP)2MnCl4@PMMA fiber membrane is 113.46nm ( Figure 6e); each fiber shows uniform size and no obvious beading and agglomeration; further illustrating the uniformity of the prepared (CTP)2MnCl4@PMMA fiber membrane. Elemental mapping shows that C, O, P, Cl, and Mn are uniformly distributed in the fiber membrane ( Figure 6 (f)
[0059] In view of the excellent optical properties of (CTP)2MnCl4@PMMA fiber film, we explored its application in the field of night display. First, wearable night vision clothing was prepared using (CTP)2MnCl4@PMMA fiber film; a large area of "SOS" and stripe patterns ( Figure 6 g); secondly, the fiber membrane was used to prepare a fluorescent bracelet ( Figure 6 h); when danger occurs at night or in other emergency situations; people wearing (CTP)2MnCl4@PMMA fiber night vision clothing can be quickly located and send out an "SOS" distress signal; it is expected to be used for rapid rescue in various emergency situations.
[0060] In addition; Figure 6 As shown in the fluorescent number "0406" shown in the figure, the prepared fiber membrane can also be used for night display. We also further explored its application in night signs. Traditional signs such as emergency exits are easily interfered by external factors, resulting in poor wiring and thus the failure of all LEDs to be successfully activated. Based on the excellent optical properties of (CTP)2MnCl4@PMMA fiber membrane, we designed a safety exit sign ( Figure 6 The sign only requires a 254nm UV chip, which is much cheaper than traditional exit signs.
[0061] In summary, the (CTP)2MnCl4 and (BTP)2MnCl4 single crystals prepared by the simple solvent evaporation method of the present invention exhibit excellent photophysical properties; they can produce bright narrow-band green light emission under ultraviolet / blue light, mechanical force and X-ray excitation; the green light emission comes from the defect-assisted four-coordinated Mn 2+dd transition. For photoluminescence, the quantum yields of (CTP)2MnCl4 and (BTP)2MnCl4 are as high as 98.5% and 88.4%. Wearable luminescent textiles prepared based on (CTP)2MnCl4@PMMA fiber film can be used for emergency rescue in various emergency situations; they can also be used for various safety signs; they are more convenient and cheaper than traditional signs. For X-ray detection, (CTP)2MnCl4 and (BTP)2MnCl4 single crystals also achieved light yields of up to 89,000 and 49,000 photons / MeV, which are better than most inorganic scintillators. For mechanoluminescence, the luminescence originates from the energy released by the recombination of electrons and holes when hydrogen bonds are broken. Flexible films prepared based on (CTP)2MnCl4 and (BTP)2MnCl4 can achieve good force-stimulated luminescence; they are expected to be used for anti-counterfeiting identification.
[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments; the above embodiments and descriptions are only for explaining the principles of the present invention; without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements; these changes and improvements fall within the scope of the present invention. The scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A metal halide with multiple excitation sources, characterized in that: The structural formula is A2[MnCl4], wherein A is CTP or BTP, CTP is (2-chlorobenzyl)triphenylphosphonium cation, and BTP is benzyltriphenylphosphonium cation.
2. A method for preparing a metal halide with multiple excitation sources, characterized in that: include Step 1: Dissolve MnCl2 and substance A in methanol at room temperature to form a clear and transparent solution; Step 2: Slowly evaporate the solution in step 1 in an oven for 48 hours to prepare a light green block A2[MnCl4] single crystal.
3. The method for preparing a metal halide with multiple excitation sources according to claim 2, characterized in that: In step 1, the molar ratio of MnCl2 to substance A is 1:
2.
4. The method for preparing a metal halide with multiple excitation sources according to claim 3, characterized in that: The temperature of the oven in step 2 is 40°C.
5. The method for preparing a metal halide with multiple excitation sources according to claim 4, characterized in that: The substance A in step 1 is any one of (2-chlorobenzyl)triphenylphosphonium chloride or benzyltriphenylphosphonium chloride.
Citation Information
Patent Citations
Method for realizing X-ray detection and imaging by using organic-inorganic hybrid metal manganese halide
CN113720866A
Organic-inorganic hybrid manganese-based halide scintillator, composite membrane, and preparation and application of organic-inorganic hybrid manganese-based halide scintillator and composite membrane
CN118185617A
Zero-dimensional manganese-based halide scintillator, preparation method and application
CN118324808A
Organic-inorganic hybrid halide perovskite material and preparation method thereof
CN119019449A
Bis(quaternary phosphonium) tetrahalomanganate salts as charge-control agents
US5512407A